An ATP-activated, ligand-gated ion channel on a cholinergic presynaptic nerve terminal. - Sun, X P (1996)
ATP has recently been identified as a fast neurotransmitter in both the central and peripheral nervous systems. Several studies have suggested that ATP can also affect the release of classical neurotransmitters, including acetylcholine with which it is co-released. We have searched for ATP receptors on a cholinergic presynaptic nerve terminal using the calyx-type synapse of the chicken ciliary ganglion. ATP was pulsed onto the terminals under voltage clamp and induced a short latency cation current that exhibited inward rectification and marked desensitization. This current was not seen with adenosine but was mimicked by several sterically restricted ATP analogs and was blocked by suramin. ATP-activated single ion channels exhibited prominent flickering and had a conductance of approximately 17 pS. Our results demonstrate a ligand-gated P2X-like purinergic receptor on a cholinergic presynaptic nerve terminal.